IDNLearn.com offers a unique blend of expert answers and community insights. Get the information you need from our experts, who provide reliable and detailed answers to all your questions.
To solve this equation, we can follow the next steps:
First: we can sum similar terms like 3x + 3x.
6(x - 1) = 3x + 3x + 6
6(x - 1) = 6x + 6
Then, solve 6(x-1) using the distributive property:
6x - 6 = 6x + 6
Subtract 6x from both sides of the equation:
6x - 6x - 6 = 6x - 6x + 6
0 - 6 = 6
-6 = 6
Since the result is not congruent, we can say that this equation has no solution.